The Historic Photo Archive of Repsol: creation and access to the digital photography collections - de Castro Leal, Leticia (Documentación de las Ciencias de la Información, 2019)
This article seeks to analyse the creation of Repsol’s Historical Archive, an essential tool for understanding the development of the hydrocarbon sector in Spain. The article also explains how to access the aforementioned Archive. The paper will first examine how the Spanish hydrocarbon sector emerged and how said sector operated after the passing of the Petroleum Monopoly Law in 1927 until Repsol’s foundation in 1987. The second part of the article will explore both the creation of Repsol’s Historical Archive, specifically its photographic section, and its inventory, filing and conservation processes. In the third section, the paper will explain how access to our archive is controlled and what steps the company is taking to promote it. Finally, the article addresses Repsol’s intention to transform its Historical Archive into a resource for society as a whole. However, this will undoubtedly be a long process, because we have to digitalise our fonds,-or archive groups-, and incorporate them into Repsol’s file management system. Futhermore, we have to comply with the General Data Protection Regulation that came into force last May.